Analysis of ionic defect distribution on perovskite photodetector by temperature-dependent deep level transient spectroscopy - Vu, Thi Kim Oanh; Nguyen, Thi Thanh Bao; Bui, Thi Thu Phuong; Nguyen, Ngoc Anh; Kim, Eun Kyu (Communications in Physics, 2024)
In this work we used temperature-dependent deep-level transient spectroscopy for the analysis of the role of additives in high-efficiency organohalide perovskite solar cells prepared by solution-based method. The ionic defect parameters like activation energy, trap density and diffusion constants for each observed ionic species were compared in different solid-state organic–inorganic metal halide perovskites. The obtained results showed that both the Carbonyldiphthalic anhydride and Hexafluoroisopropylidene diphthalic anhydride additives have significantly passivated deep level trap density, consequently enhance perovskite solar cell performance.